The Effect of Hot Water Treatment and Dose Trichoderma sp. to Plant Tissue of Seedling Growth from Bud Chips of Sugarcane (Saccharum officinarum) - Haryuni - (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2015)
Sugarcane (Saccharum officinarum) is a high-value economical crops, only grows in tropical climates of Java and parts of Sumatra. Ratoon stunting disease (RSD) is a vascular disease in sugarcane which its visual symptoms is difficult to detect. The disease has spread across the sugarcane plantations in Indonesia with the percentage of attacks 10-100%. The use of buds chips treatment of seedling plant is an act of reducing pathogen development. The research effect of hot water treatment / HWT (0, 30, 60, and 90 min) and dose application of Trichoderma sp. (0, 25, and 50 g) using 864 varieties, is designed with a completely randomized factorial design. The results showed that Trichoderma sp. able to infect the roots and stems of seedling age 3 months, part of plant tissue increase of protein and proline content, decrease of glucose content so that increase resistance and health in the growth of sugarcane seedling before planting in the land.Tanaman tebu (Saccharum officinarum) adalah tanaman yang bernilai ekonomi tinggi, hanya tumbuh di daerah beriklim tropis terutama di Jawa dan sebagian Sumatra. Penyakit ratoon stunting disease (RSD) merupakan penyakit pembuluh pada tebu yang sulit dideteksi gejala visualnya. Penyakit tersebut telah tersebar di seluruh pertanaman tebu di Indonesia dengan presentase serangan mencapai 10-100%. Penggunaan bahan tanam benih asal mata tunas (bud chip) dapat mengurangi perkembangan patogen. Penelitian pengaruh waktu perendaman air panas (0, 30, 60, dan 90 menit) dan aplikasi dosis jamur Trichoderma sp (0, 25, dan 50 g) terhadap pertumbuhan benih tebu klon 864, dirancang dengan menggunakan rancangan acak lengkap faktorial. Hasil penelitian menunjukkan bahwa jamur Trichoderma sp mampu menginfeksi bagian akar dan batang benih umur 3 bulan, pada bagian jaringan tanaman terjadi peningkatan kadar protein dan prolin serta penurunan kadar glukosa sehingga meningkatkan ketahanan dan kesehatan pada pertumbuhan awal benih tebu sebelum ditanam di lahan.